Flexible plate printing backflow carrier - FU XIANGCHENG; DING JIANQIN (2020)
Reflow soldering is an essential process in SMT (Surface Mount Technology) production, and in order to prevent an FPC (Flexible Printed Circuit) from deviating or deforming, the FPC is usually mountedon a reflow carrier. According to an existing SMT printing backflow carrier, the placement position of a magnet is designed in advance according to different FPC models; the high-temperature magnet is implanted into the carrier, then the carrier is covered with the magnetic steel sheet with the window position formed in advance according to the FPC model to fix the FPC, the operation mode does not share the carrier, the carrier cannot be maintained after being damaged, and the cost investment is large. According to the utility model, a reverse positioning mode is adopted, so that a through hole for flexible plate positioning does not need to be formed in the carrier plate, the universality of the carrier plate is improved, and meanwhile, the positioning base plate is convenient to maintain by adopting the high-te